Potato virus X-mediated constitutive expression of Plutella xylostella PxSDF2L1 gene in Nicotiana benthamiana confers resistance to Phytophthora parasitica var. nicotianae - Ivis Moran-Bertot; Lianet Rodríguez-Cabrera; Orlando Borras-Hidalgo; Siliang Huang; Yunchao Kan; Denis J. Wright; Camilo Ayra-Pardo (BMC Plant Biology, 2021)
Abstract Background The Plutella xylostella PxSDF2L1 gene was previously reported to enhance insect resistance to pathogen at high basal transcription rate. PxSDF2L1 shows similitude with the stromal cell-derived factor 2 (SDF2), an ER stress-induced chaperon protein that is highly conserved throughout animals and plants. The precise biological function of SDF2 is not clear, but its expression is required for innate immunity in plants. Here, we investigate whether a continuous expression of PxSDF2L1 in Nicotiana benthamiana can similarly confer resistance to plant pathogen, particularly, the black shank Phytophthora parasitica var. nicotianae. Results The N. benthamiana plants were inoculated with agrobacteria transformed with a PVX-based binary vector carrying the PxSDF2L1 gene; similar agroinoculation experiments with a PVX vector carrying the GFP gene were used for controls. In pot trials, agroinfected N. benthamiana plants constitutively expressing PxSDF2L1 showed a significant reduction of stem disease symptoms caused by the inoculation with P. parasitica, compared with controls. Conclusions We confirm a role of PxSDF2L1 in resistance to black shank, with a potential application to engineering active resistance against this oomycete in the commercial N. tabacum species and propose its evaluation in other crop families and plant pathogens.